Instructional Leadership Based On Theory Of Planned Behaviors In Improving Nuring Students 'Commulative Achievement Index - Margaretta, Sheylla Septina; Isnaeni, Ely (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The method used is a quantitative method using a pre-experimental design with the type of one group pre-post test, the application of instructional leadership is carried out by the Head of Study Program for one semester with the GPA assessment using observations through the GPA transcript value. The sampling design used a total sampling technique, namely 63 students in semester 1. The results of the study through the paired t-test obtained a significant value of p = 0.000 on the student's GPA. The conclusion of this study is that the application of Instructional Leadership with the TPB approach can increase student GPA. This research can be applied by the Head of Study Program in carrying out its duties and functions so that it can improve student academic achievement